Analysis of Brand Equity and Supply Chain as a Determinant of Voting Intention in Young Constituents in the city of Bandung, Indonesia - Tongam Sirait; Marcellia Susan (International Journal of Supply Chain Management, 2019)
This study analyzed political parties using marketing theory, especially supply chain management and political brands using the Customer Base Brand Equity (CBBE) approach. The political brand in this study can determine what factors are in the minds of voters or the mindset of the people that influence their behavior to produce brand equity that can be communicated and presented to the constituents so that the impact drives them towards electoral choices in certain parties. This study looks at the influence of variables in the form of Party Socialization Process, Supply Chain Strategy, Party Knowledge (which consists of party awareness and party association), party perceived quality on the formation of Voting Intention of young constituents in political parties in Indonesia, especially in the city of Bandung. This research is an Explanatory study with quantitative methods that are descriptive to explain the research in-depth. Samples were conducted as many as 431 respondents from the city of Bandung aged 17-30 years who already have a KTP and have the right to vote with the help of the SPSS software. The results of the study found that an increase in the Party socialization process on Brand Equity, in this case, is Party Knowledge (party awareness and party association), and party perceived quality would increase the voting intention of young constituents in the city of Bandung. Therefore, research is needed especially for decision-makers in political parties in order to increase their brand equity and supply chain orientation so that it affects the increase in the voting intention which then affects the results of their votes in the coming election, especially by using political brand theory with CBBE approach.